Pengaruh Kualitas Pelayanan dan Kepercayaan Terhadap Kepuasan Nasabah Bank Rakyat Indonesia Syariah (Studi Pada Bank Rakyat Indonesia Syariah Cabang Darussalam Banda Aceh) - Vabiola Ghantynireta, Bunga; Inayatillah, Inayatillah; Evriyenni, Evriyenni (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This study aims to determine the effect of service quality and trust on customer satisfaction at Bank Rakyat Indonesia Syariah Darussalam branch, Banda Aceh. This study uses a quantitative approach using multiple regression analysis. The sampling technique in this study was random sampling. Data collection techniques in this study by distributing questionnaires to 100 respondents. The results of this study indicate; (1) the service quality variable has no effect on customer satisfaction, (2) the trust variable has a positive and significant effect on customer satisfaction, and (3) together service quality and trust have an effect on customer satisfaction